SOFT SYSTEM METHODOLOGY (SSM) APPROACH TO ADDRESS ORGANIZATIONAL INEFFICIENCIES IN HUFF AND PUFF OPERATIONS - Faizal Ardi Warsiyanto; Yos Sunitiyoso; Budiarso Budiarso (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The success of maintaining production in heavy oil fields is highly dependent on the effectiveness of Huff and Puff operations. However, in practice, this effectiveness is often hampered by technical limitations, budget constraints, organizational incompatibilities, and administrative inefficiencies. This study highlights issues at PT Energi Mega Persada (EMP), where a lack of communication and coordination between the engineering team, field teams (production and well service), and support functions (finance, procurement, and SHE) creates significant operational barriers. Each function has different priorities engineering focuses on reservoir optimization, field teams on operational execution, and support functions on regulatory compliance and budgeting but there is no integrated mechanism to align these priorities. This research uses Soft Systems Methodology (SSM) as a managerial approach to analyze organizational dynamics and identify root causes from the perspective of various stakeholders. Through systemic mapping of inter-functional conflicts and barriers, SSM enables the development of an integrated strategy that integrates technical and managerial decisions. The analysis results show that operational success is not solely determined by technology, but also by cross-functional collaboration, adaptive leadership, and integration between corporate strategy and operational conditions in the field. The application of SSM helps EMP formulate a more efficient, responsive, and aligned coordination framework with long-term production goals.